Can immunogenetics illuminate the diverse manifestations of respiratory infections? - Affandi, J.; Price, Patricia; Waterer, G. (2010)
Improved technologies for high-throughput genotyping and the establishment of well-defined cohorts prompted hope that polymorphisms would be discovered that define a patients' risk of respiratory disease or aid in diagnosis. Genetic pitfalls encountered in this quest include genotyping errors, ethnic differences and linkage dysequilibrium. Differences in the definition of the disease phenotype also create discrepancies, so immunogenetic testing has not yet reached the clinic. However, associations between a polymorphism and a disease phenotype place the gene or one in linkage dysequilibrium on the path to the disease. Here we review studies of immune-related genes that are illuminating the immunopathogenesis of community-acquired pneumonia and mycobacterial infections. © 2010 The Author(s).